Circular RNAs in Intervertebral Disc Degeneration: An Updated Review - Xu, Derong; Ma, Xuexiao; Sun, Chong; Han, Jialuo; Zhou, Chuanli; Wong, Sunny Hei; Chan, Matthew T. V.; Wu, William K. K. (Frontiers in Molecular Biosciences, 2022)
Low back pain, a common medical condition, could result in severe disability and inflict huge economical and public health burden. Its pathogenesis is attributed to multiple etiological factors, including intervertebral disc degeneration (IDD). Emerging evidence suggests that circular RNAs (circRNAs), a major type of regulatory non-coding RNA, play critical roles in cellular processes that are pertinent to IDD development, including nucleus pulposus cell proliferation and apoptosis as well as extracellular matrix deposition. Increasing number of translational studies also indicated that circRNAs could serve as novel biomarkers for the diagnosis of IDD and/or predicting its clinical outcomes. Our review aims to discuss the recent progress in the functions and mechanisms of newly discovered IDD-related circRNAs.